The reality of monetary policy in Algeria during the period 2010-2017 - Allem , Asma; Allem, Fatima (Social Empowerment Journal, 2020)
The monetary policy is one of the basic pillars on which the economic policy is based. it is used to achieve the objectives of the latter, as the central bank follows a specific strategy by using the various tools available in order to achieve the desired and established goals of the economic policy. The aim of this research paper is to shed light on the reality of monetary policy in Algeria, by highlighting the development of the monetary mass and its interviews, inflation and economic growth rates during the period 2010-2017.To conduct this research, the researcher choses an analytical approach. The study concluded that achieving monetary stability in the monetary market in Algeria is about the path of changes in the growth rates of the monetary mass, which is due to important reasons, including the development of banking conditions.As well as the desire of the Bank of Algeria to try to control bank liquidity, and that the monetary policy in Algeria is working to organize bank liquidity to reduce inflation, but it is necessary to activate the production system and make it more elastic aggregate demand growth and the elimination of price increases.